Socialization of Accounting Records and Financial Reports Preparation Using Several Alternative Software - Ferry Kosadi; Wajib Ginting (Universitas INABA, 2024)
The aim of this activity is to improve the technical skills of participants, especially in the process of managing accounting data and preparing financial reports through various alternative software and preparing participants' involvement in activities with MSMEs. The main obstacle faced is technical problems related to tracking troubleshooting when the software process is disrupted, or the results of the process are not as they should be. Repeated software usage training will provide better abilities along with an understanding of the characteristics of each software used. Participants can understand the database as the main part of an information system well, but the technical preparation of the database structure still requires further socialization. Participants' interest and confidence in contributing to community services activities showed a very good response so that in future activities it is hoped that their involvement can continue to be increased by previously carrying out orientation and conditioning on certain software.